2013
DOI: 10.1111/jce.12074
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Ventricular Repolarization Dynamics in Patients with Early Repolarization Syndrome

Abstract: ERS patients had a continuously depressed diurnal and nocturnal adaptation of the QT interval to the heart rate. Such abnormal repolarization dynamics might provide a substrate for reentry and be an important element for developing ventricular fibrillation in the ERS cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…15 Indeed, β-blockers decrease the QT/RR slope in daytime, and not at nighttime, whereas sympatho-excitation increases the QT/RR slope. 14,25 In our study, in the LGE(+) patients, the QTe day/night and QTa day/night ratios were significantly greater than those in the LGE(−) patients. On the other hand, low QTe day/night and QTa day/night ratios were observed in the LGE(−) patients.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…15 Indeed, β-blockers decrease the QT/RR slope in daytime, and not at nighttime, whereas sympatho-excitation increases the QT/RR slope. 14,25 In our study, in the LGE(+) patients, the QTe day/night and QTa day/night ratios were significantly greater than those in the LGE(−) patients. On the other hand, low QTe day/night and QTa day/night ratios were observed in the LGE(−) patients.…”
Section: Discussioncontrasting
confidence: 61%
“…Indeed, it has been shown that the QT/RR slope is significantly increased in patients with organic heart disease [6][7][8][9][10] whereas it is remarkably decreased in patients with idiopathic ventricular fibrillartion. [11][12][13][14] Thus, both CMR imaging and QT dynamicity are expected to be powerful tools for risk stratification of SCD.…”
mentioning
confidence: 99%
“…showed that the QT/heart rate relationship was reduced in BrS patients with L‐type Ca channel mutations compared to the controls. Recently, we have found that compared to a control group, ERS patients have impaired QT‐rate dependence suggesting that such a repolarization heterogeneity may provide a baseline substrate for reentry in ERS patients …”
Section: Discussionmentioning
confidence: 99%
“…The QT intervals were automatically measured using the CM5 lead, and a visual review was always performed to confirm the correct measurement of the QT intervals. We described the method previously; briefly, after conversion of the 24‐hour recordings into 2,880 templates sampled at 30‐second intervals, the intervals with ≤80% eligible QRS complexes were considered as ectopy or noise and therefore eliminated. The average QT intervals were then measured automatically at the apex (QTa) of the T wave, where the peak of the parabola was fitted to the highest amplitude change after the QRS and, at the end of the T wave (QTe), defined as the intersection of the tangent to the downslope of the T‐wave and the isoelectric line.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation